POLEMIK WACANA KANTOR URUSAN AGAMA (KUA) MENJADI TEMPAT PERNIKAHAN DAN PENCATATAN SEMUA AGAMA - IKBAL SULAIMAN (GANEC SWARA, 2024)
The idea of making the Office of Religious Affairs (Kantor Urusan Agama, KUA) a marriage registry for all religions in Indonesia has sparked significant debate. The Office of Religious Affairs (KUA) is a government institution responsible for the development and guidance of religious life in the community. The role of the KUA as a marriage registry for all religions has been the subject of intense debate in recent years. The Ministry of Religious Affairs' initiative to make the Office of Religious Affairs an inclusive center for religious services has attracted much controversy. This study aims to analyze the social and cultural impact of the implementation of the discourse, taking into account the potential for increased interfaith tolerance as well as the risk of conflict that may arise and analyzing the social and cultural impact of the implementation of the KUA as a place of marriage registration for all religions. The results show that this discourse raises pros and cons from various figures. If the KUA successfully transforms into an institution that serves all religions, it may trigger a cultural paradigm shift in society. People may become more open to other religious practices and reduce the negative stigma against religious minorities. This could be the first step towards a more inclusive society. On the other hand, there is a risk that integrating these services could lead to a blurring of each religion's identity. Some groups may feel that their religious traditions and practices are no longer valued or fully recognized in the context of these shared services.  This research uses a type of normative legal research, which conducts research on library legal materials or secondary data. Normative legal research examines positive legal norms in the form of laws and regulations, this research explores the views of the community and religious leaders regarding the change in the function of the KUA, as well as the steps needed to implement this policy effectively